(3GdJfHjg Ydi GdCSHGH GdJi ChLHJ GdGNJdGa Hjf GdeSdejf aj BQGFges - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3GNHQfG Gdabjg GdaGVd CHh ESMGb EHQGgje Hf eMeO GdeJbf GdSHJi bOe YdjfG KZQ GdEScfOQjI bGd GdMeO ddg eSHZ GdfYe s
(3BNQgG (B:s
(3hhLhg GdbQBf GdSHY hfMh Pdc agPg CSHGH GdNdGa GdhbGY Hjf GdCeI bO fHgJ YdjgG Je LejY GdcJGH HMeO Gddg hYhfg s
(3QhGjI CHh ESMGb GHQGgje Hf eMeO GdeJbf Hf EHQGgje GdSHJi GddNeis
(3HChdg bQGAI SfI (B554 (3hHBNQgG bQGAI ai GdSfI GdePchQs
(3Ke SeGY Ydi GdfSNI Gdefbhd efgG JGQjNg (B523 (3SfIs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda SfI (B516 (3HHdfSHIs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds